A Comparative analysis of Bankruptcy prediction models: Altman’s Model and Zmikewski’s Model in EGYPT - Mahmoud, Mahmoud Elsayed; Arifin, Taufiq (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2024)
This study provides a comparative analysis of two widely used bankruptcy prediction models—Altman’s Z-Score Model and Zmijewski’s X-Score Model—applied to companies listed on the Egyptian stock market. The sample comprises 10 companies, split evenly between financially distressed firms and financially stable ones, with data spanning from 2020 to 2022. The predictive accuracy of both models was assessed, with Altman’s Z-Score achieving a predictive ability of 50%, while Zmijewski’s X-Score demonstrated a slightly lower accuracy at 46.66%. The findings indicate no significant difference in the predictive capabilities of the two models within the context of the Egyptian market. These results suggest that neither model is distinctly superior, highlighting the need for further research to refine bankruptcy prediction methods in emerging markets like Egypt.